Development of Ficus carica Linn leaves extract incorporated chitosan films for active food packaging materials and investigation of their properties - Yilmaz, P.; Demirhan, E.; Ozbek, B. (ELSEVIER, 2022)
The serious problems caused by extensive usage of petroleum-based plastic materials led to investigating the comprehensive studies and developing active food packaging materials. Even if the chitosan-based films are considered an attractive source, they exhibit some practical difficulties in developing active food packaging applications. Hence, Ficus carica Linn leaves extract (FLE), with the features of its cheapness, easy accessibility and superoxide anion radical scavenging activity, was incorporated into chitosan (CS) film at various concentrations (2%-6% w/w). To the best of our knowledge, this was the first time that FLE was utilized as a bioactive substance incorporated into chitosan films to develop eco-friendly, biodegradable, active food packaging material. The results obtained revealed that FLE incorporation into chitosan films significantly improved the swelling, water solubility and opacity of neat chitosan films. FTIR and morphological analysis indicated that the films produced exhibited smooth structure with homogenous dispersion of FLE. In mechanically, the addition of FLE resulted in a significant reduction in tensile strength while the elasticity of the films was improved. Additionally, the antioxidant and biodegradability properties of neat chitosan films were enhanced significantly. It was concluded that CS-FLE films appeared to be a capable and enhanced option for synthetic polymer-based food packaging materials. Based on the analyses performed, further studies are suggested on the packaging application for various foods and to evaluate the possible interaction of packaging film materials with the compounds of the food products, to avoid possible negative effects.
Keywords: Ficus carica Linn leaves extract; Chitosan films; Antioxidant activity; Soil biodegradability; Active food packaging materials; ANTIOXIDANT; LEAF; Food Science & Technology